2009
DOI: 10.1017/s0022112008004886
|View full text |Cite
|
Sign up to set email alerts
|

A fundamental limit on the balance of power in a transpiration-controlled channel flow

Abstract: This paper is a direct sequel to Bewley & Aamo (J. Fluid Mech., vol. 499, 2004, pp. 183–196). It was conjectured in that paper, based on the numerical evidence available at that time, that the minimum drag of a constant mass flux channel flow might in fact be that of the laminar flow. This conjecture turned out to be false; Min et al. (J. Fluid Mech., vol. 558, 2006, 309318) discovered a curious control strategy which in fact reduces the time-averaged drag to sub-laminar levels. The present paper establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 6 publications
3
40
0
Order By: Relevance
“…The absolute maximum of drag reduction for A + = 12 is found to be R = 0.48, which is not far from relaminarization. (At this value of Re, about one-quarter of the friction drag is the laminar contribution, which has been demonstrated by Bewley [25] to be the true minimum one can reach. At lower Re, waves at A + = 12 have been found to relaminarize the flow.…”
Section: Streamwise-travelling Wavesmentioning
confidence: 57%
“…The absolute maximum of drag reduction for A + = 12 is found to be R = 0.48, which is not far from relaminarization. (At this value of Re, about one-quarter of the friction drag is the laminar contribution, which has been demonstrated by Bewley [25] to be the true minimum one can reach. At lower Re, waves at A + = 12 have been found to relaminarize the flow.…”
Section: Streamwise-travelling Wavesmentioning
confidence: 57%
“…Bewley [33] extended his earlier analysis of channel flow subject to blowing and suction at the wall and modified the above-mentioned conjecture. He showed that energetically (that is, considering the total power, accounting for both the power saved and the additional power for control input, for a given mass flux) the best one can do is to maintain a laminar flow.…”
Section: Limitation Of Control Performancementioning
confidence: 92%
“…A theoretical limit of the active friction drag reduction control, i.e. the relationship between drag reduction effect and input power, for control of a plane channel (Bewley, 2009) and of arbitrary ducts was discussed ). The existence of such a limit for the external flows, however, is still unclear.…”
Section: Introductionmentioning
confidence: 99%